Regional mathematical contests: experience and perspectives - Apynis, Antanas; Kašuba, Romualdas; Stankus, Eugenijus (Lietuvos matematikos rinkinys, 2011)
A regional competition can inspire students to greater achievement. We are eager to challenge their math skills and motivation using interesting but really accessible problems. Considerable attention is paid also to the formulation of tasks. So even some local facts and or other well-known notions might also become a reasonable element of a problem.
Keywords: contests; problems; geometry; combinatorics; divisibility of integers; proofs